THE APPLICATION OF GOOGLE CLASSROOM IN LEARNING ENGLISH: STUDENTS’ INTERESTS - Puspita Sari Nasution; Utami Dewi (English Education : English Journal for Teaching and Learning, 2021)
This study aimed to describe students’ interests in the application of Google Classroom (GC) in learning English. The subjects of this study were ten students of the Religious Department who learn English subject. The instruments of data collection were questionnaires and interviews. The data were analyzed by using the theory of Miles and Huberman. The results showed that students’ interest in learning by using online through Google classroom has four aspects include: (1) The students felt happy in learning English using Google Classroom was 60 %; (2) The students had a strong interest in using Google classroom in learning English was 50%; (3) The students gave strong attention in the process of using Google classroom was 40%; and (4) The students actively involved in using google classroom was 50%.